(untitled) (Diametros, 2005)
The subject of the article is a comparison of the work of Heraclitus with the utterances of Delphic oracle. The author analyzes the character of those utterances, pointing to their “two-layeredness”, i.e. to their having two meanings: one litteral – apparent and the other hidden – proper. The proper meaning is allegoric and is in such a relation to the litteral as the latter is to the sign (a material text). To settle for the litteral meaning is a mistake that makes it impossible understand the prophecy properly. Some essential fragments of Heraclitus have a similar character – they also have both an apparent sense (often paradoxical) and a proper, hidden sense. One can guess that the philosopher intentionally made his work resemble Pythia’s utterances to give it a unique status. The pattern [sign/apparent meaning = apparent meaning/hidden meaning] can be also suitable for Heraclitus’s vision of the world (the phenomena are in such a relation to the Logos as the litteral sense of the prophecy is to the allegoric sense). The relation that appears in each of these three areas is a peculiar kind of “indicating”.